Financial Analysis of Waqf Real Estate Revenues in the West Bank: 1994-2014 - Musaee, Anwar H. M; Abbas, Eeman Muhammad; Mujani, Wan Kamal; Sidek, Roziah Sidik @ Mat (Asian Economic and Financial Review, 2014)
This paper made a financial analysis of the revenues of the Palestinian Ministry of Waqf ( endowment ) and specifically its real estate revenues in the West Bank. It was found that 61% of the waqf ministry's total revenues were from real estate. This clearly shows the importance of waqf real estate rentals in the ministry's annual budget. The importance of this study springs from its dependence on primary sources: Palestinian Ministry of Waqf’s financial records, and its West Bank directorates ' 2,108 files related to real estate leasing. This was in addition to personal interviews with waqf ministry officials and experts from outside the ministry. In order to achieve the purpose of this study ( finding out the factors impeding the development / investment of the ministry's real estate low revenues), the researcher computed the collected data of the leased waqf real estate using the descriptive analytical method. After data analysis, it was found that the West Bank was home to a large number of leased waqf real estate but its revenues were low compared to its size and locations. It was also found that the ministry had a big problem in collecting rentals from the tenants. In 2013, the ministry only managed to collect 1,264,372 Jordanian dinars, though the actual value of dues was JD 4,599,631. In other words, the ministry managed to collect 27% of all dues. The rest remained debts and revolving balance on the tenants. This situation was due to the waqf real estate leasing mechanism pattern of contracts regulating them, the legal extension of leasing contracts, freezing of rental charges, low collections, accumulation of debts on tenants, and legal legislations.